Disruptive, yet inclusive AI: solution and boundaries from a labour law perspective. - Federica Palmirotta (Italian Labour Law e-Journal)
The contribution focuses on the pursuit of inclusive AI application that not only outweigh the risks AI poses but actively commit to workers’ well-being and to fundamental rights, such as the right not to be discriminated against, also thanks to the involvement of all stakeholders from the outset. To this end and from a labour law perspective, the essay offers a conceptualization for the notion of inclusive AI at work and provides some examples, in order to assess their legal status in the risk pyramid within the recent Regulation (EU) 2024/1689. Secondly, it analyses regulatory techniques that can be mobilized within the European legal landscape to enforce this inclusive prerogative, since they impose an active duty on the employer to prevent and remove discrimination, thereby ensuring inclusion.